1967
DOI: 10.2134/agronj1967.00021962005900040022x
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Paraquat‐Induced Chlorosis with Phaseolus Foliar Tissues1

Abstract: Bioassay procedures with leaf disks from Phaseolus vulgaris L., Indian bean, were used to determine factors influencing ( 1,1′‐dimethyl‐4,4'bipyridinium) paraquat activity. Relative phytotoxicity was determined by varying herbicide levels from 0 to 1.0 ppm ai with light intensity, temperature and reaction time. Reduction of extractable chlorophyll was closely related to increased paraquat concentrations. Increased time, temperature and light intensity accelerated rate and magnitude of leaf disk chlorosis induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1968
1968
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…INTRODUCTION N UM EROUS investigations have provided abundant data on the competitive ability of weeds. Considerable weed competition research in crop species has dealt with weeds and their influence on cereal grains (2,8,11,14,16), flax (Linum usitatissimum L.) (1,3,16), and sorghum (Sorghum bicolor (L.) Moench) (20). The critical period of weed competition has been a common objective in many weed-crop competition studies (6,7,9,10,12,13,17).…”
Section: Weedmentioning
confidence: 99%
“…INTRODUCTION N UM EROUS investigations have provided abundant data on the competitive ability of weeds. Considerable weed competition research in crop species has dealt with weeds and their influence on cereal grains (2,8,11,14,16), flax (Linum usitatissimum L.) (1,3,16), and sorghum (Sorghum bicolor (L.) Moench) (20). The critical period of weed competition has been a common objective in many weed-crop competition studies (6,7,9,10,12,13,17).…”
Section: Weedmentioning
confidence: 99%
“…Any effect of nitrogen on the retention of paraquat by the leaves was specifically excluded, by applying drops of herbicide to the horizontal surface of short segments of leaves. This type of technique was used by Barnes & Lynd (1967) in their investigations into the activity of paraquat applied to leaf discs of Phaseoliis vidgaris L., and by Hodnett (1968) who studied the uptake of diquat by leaf discs of the same species.…”
Section: Introductionmentioning
confidence: 99%
“…However, on winter annual weeds, injury rate was positively associated with overall control; shoot biomass reduction of horseweed and purple deadnettle was 34% and 28% greater, respectively, under the warmer temperature regime. Greater absorption of paraquat by kidney bean (a summer annual) was ascribed to an increase in cell-membrane permeability at elevated temperatures (Barnes and Lynd 1967;Merkle et al 1965). In the winter annual hare barley [Hordeum leporinum (Link) Arcang.…”
Section: Temperaturementioning
confidence: 99%
“…Air temperature also influences paraquat efficacy. For example, injury to kidney bean (Phaseolus vulgaris L.) increased concomitantly with temperature (Barnes and Lynd 1967;Merkle et al 1965). On horseweed, Eubank et al (2012) observed poor control (30% to 50%) from applications at 8 C compared with 16 C (72% to 88% control).…”
Section: Introductionmentioning
confidence: 99%